Tuning the solid-state emission by co-crystallization through σ- and π-hole directed intermolecular interactions. Issue 12 (28th February 2019) - Bhowal, Rohit; Biswas, Suprakash; Adiyeri Saseendran, Devi Prasad; Koner, Apurba L.; Chopra, Deepak
Abstract : σ- and π-hole directed intermolecular interaction driven tuning of luminescence. Abstract : Four new binary luminescent co-crystals and a co-crystal stoichiomorph comprising aromatic compounds and 1, 4-diiodotetrafluorobenzene were successfully synthesized by the solvent drop grinding method. Structural features of these co-crystals indicate that the relative interplay of σ- and π-hole directed intermolecular interactions were observed to be responsible for modulating luminescence properties of those materials. Investigation of photoluminescence properties reveals that there is a substantial change in emission color from the starting aromatic materials to co-crystals. The I⋯N and σ-hole⋯π halogen bonds along with π-hole⋯π interactions have been instrumental towards altering the emissive properties of the luminescent materials.